Peculiarities of Quality Management System in Higher Educational Institutions - JUMASHEVA, Sulushash; BAIMUKHANOVA, Sariya; RAZAKOVA, Dina; SEITKHAMZINA, Gaukhar (Journal of Advanced Research in Law and Economics, 2018)
The important task facing Kazakhstan is to enter the top 30 competitive countries in the world. Modern universities had tasked to further improve the quality of education, including creation of effective system of quality assurance, modernization of the content of higher and postgraduate education in line with international trends. In this connection, an objective need arises for qualitative transformations in the sphere of preparing specialists in various fields of economic activity. The purpose of the research is to review the main directions of the theory on quality assurance in higher education; to examine the main directions of quality assurance in Kazakhstan on a country level; to examine the state of art with internal quality assurance in three Kazakhstani universities. There has been developed a model for internal quality assurance in higher educational institutions. The research can be classified as descriptive based on the study of three cases, with data collected from semi-structured interviews and secondary sources. The experiences shared in this paper would be useful to other universities in the management of quality.